Passing to América : Antonio (née María) Yta's transgressive, transatlantic life in the twilight of the Spanish empire - Abercrombie, Thomas Alan, 1951- (The Pennsylvania State University Press, 2018)
"A historical biography of Don Antonio Yta, denounced in 1803 as a woman masquerading as a man. Examines the sex/gender complex within the Spanish Atlantic empire"--Provided by publisher